2012
DOI: 10.22358/jafs/66126/2012
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive evaluation of foliage from fodder trees and shrubs characteristic of Algerian arid and semi-arid areas

Abstract: The chemical composition and digestibility of foliage from nine browse plant species (Artemisia herba-alba, Atriplex halimus, Acacia nilotica, Acacia horrida, Acacia saligna, Faidherbia albida, Albizia julibrissin, Vicia faba and Punica granatum) grown in arid and semi-arid areas of Algeria were evaluated. Feed components were determined by proximate analysis, whereas phenolic and tannin compounds were analysed by colorimetric procedures and their activity tested using a biological assay. Digestibility was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The mean DM content obtained from this study was similar to those reported by Yavuz (2007) and Ogunbosoye and Babayemi (2012) of some browse plants. The DM results were also comparable to DM values obtained by Bouazza et al (2012) on some forages in Algeria. Relatively, the DM content of the shrubs was higher than that obtained by Gonzalez-Garcia et al (2009) on Leucaena leucocephala cultivars in both dry and wet seasons.…”
Section: Estimated Ddm Dmi and Rfv Of The Shrubssupporting
confidence: 86%
See 1 more Smart Citation
“…The mean DM content obtained from this study was similar to those reported by Yavuz (2007) and Ogunbosoye and Babayemi (2012) of some browse plants. The DM results were also comparable to DM values obtained by Bouazza et al (2012) on some forages in Algeria. Relatively, the DM content of the shrubs was higher than that obtained by Gonzalez-Garcia et al (2009) on Leucaena leucocephala cultivars in both dry and wet seasons.…”
Section: Estimated Ddm Dmi and Rfv Of The Shrubssupporting
confidence: 86%
“…There was significant (p< 0.05) variation of crude fat content among the shrub species. Similar variations in chemical composition have been reported for some fodder trees and shrubs of Algerian arid and semi-arid areas (Bouazza et al, 2012). This could partly be due to the physiological and genetic differences of the shrubs and also the bioclimatic conditions.…”
Section: Mean Proximate Compositionsupporting
confidence: 80%
“…were also identified by Kabbash and Shoeib (2012), as also two phenolic glycosides, one ecdysteroid, one megastigmane and two methoxylated flavonoid glycosides. Tannin, alkaloid, saponin, lignin and fiber contents were relatively low, while proteins were detected in moderately high levels and were associated with high digestibility (Benhammou et al, 2009;Bouazza et al, 2012). Also interesting to point out is that the concentrations of bioactive constituents vary within the growing season, reaching high protein and low fiber levels during February to April and low protein and high fiber levels during August and October (El-Shatnawi and Mohawesh, 2000).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…A. halimus is a nutritious plant, rich in dietary fiber (cellulose), with its fiber-rich content, it facilitates digestion (16) . Furthermore, chromium-magnesium salts contained in A. halimus evidenced as an insulin cofactor to facilitate glucose entry into muscle and fat cells (32) .Proteins were detected in moderately high levels on the leaves of A. halimus and were associated with high digestibility (33) . The present study discussed about the antidiabetic effects of A. halimus leaves powder on normal and alloxan-induced-diabetic at a dose of (150 mg per kg) rats during 28 days.…”
Section: Discussionmentioning
confidence: 99%